Nucleic Acid-Based Therapy Approaches for Huntington's Disease - Tatyana Vagner; Deborah Young; Alexandre Mouravlev (Neurology Research International)
Huntington's disease (HD) is caused by a dominant mutation that results in an unstable expansion of a CAG repeat in the huntingtin gene leading to a toxic gain of function in huntingtin protein which causes massive neurodegeneration mainly in the striatum and clinical symptoms associated with the disease. Since the mutation has multiple effects in the cell and the precise mechanism of the disease remains to be elucidated, gene therapy approaches have been developed that intervene in different aspects of the condition. These approaches include increasing expression of growth factors, decreasing levels of mutant huntingtin, and restoring cell metabolism and transcriptional balance. The aim of this paper is to outline the nucleic acid-based therapeutic strategies that have been tested to date.